The Emergence of Political Currents Among the Muslims of Eastern Transcaucasia in the early 20th century - Harutyunyan, Anush (History and Culture, 2022)
The emergence of different ideological currents and political organizations in the early 20th century among the Muslim intelligentsia of the Eastern Transcaucasia was a consequence of the socio-economic crisis of Russian Empire, the revolutionary movement, the spread of pan-Turkism and pan-Islamism, the Armenian-Tatar clashes. Three main currents were formed: social-democratic, liberal and nationalistic. The emergence of the social-democratic trend was associated with the Russian Social Democratic Labour Party’s (RSDRP) Committee of Baku and later with the formation and activity of "Hummet" party. In Soviet historiography "Hummet" was considered a RSDRP’s branch, while modern Azerbaijani authors consider "Hummet" a separate party. "Hummet" had a wide range of activities to involve Tatars in the strike movement and was able to take not only a large number of Tatars, but also Persians, into its side. During the revolution of 1905-1907, a liberal movement arose, the activation of which was connected with two factors: the Movement for the defense of the rights of all Muslims in Russia and the activity of Cadet Party in Transcaucasia. The liberal movement pursued the goals of equalizing the rights of Muslims and Christians, education in the native language and enlightenment, while the maximum demand for local administration was cultural autonomy. As a result of the Armenian-Tatar clashes the nationalist trend emerged. "Heyrat" and "Defai" parties were formed, "Hayat" newspaper was published, which disseminated the ideas of pan-Turkism and pan-Islamism, which were sharply directed against Armenians. Later the "Musavat" party was formed.